THE DYNAMICS OF EFL TEACHING IN INDONESIA: BE INNOVATIVE TEACHERS THROUGH SOCIAL MEDIA - Rita Inderawati (English Language Teaching and Research, 2017)
Technology is being used in the 21st century where teaching and learning occurs. It becomes the key component of a sophisticated classroom; nevertheless, technology is nothing in the teaching and learning without being touched and used by teacher and students.  It such a cyclical process where the teacher and the students are constantly being dynamics, to shift and change over time. Technology has a broad meaning. Making use of LCD and laptop as a favorite device for teaching is also technology. Do these tools create dynamic teachers? English language teaching entails more devices. This globalization era introduces students with internet-based activity. Having a hand phone at hand, students are able to interact with others through internet connection. They recognize kinds of social media and they have the accounts as well. This paper elaborates how Facebook group and its features become a comfortable place for teacher and students to interact dynamically by writing, reading, and giving feedback. Key words: technology, dynamic EFL, innovative teachers, social media.